Quality Assurance for Interpreting Processes - Kalina, Sylvia (Meta)

(untitled) (Les Presses de l'Université de Montréal, 2005)
AbstractThis article discusses how the quality issue in conference interpreting can be approached using a scheme for quality assurance. Participants in conferences have different roles and not always the same preferences, while interpreters depend on speakers and may have to work for heterogeneous audiences. On the basis of a model of mediated multilingual conference communication, interpreting processes and conditions can be analysed with the aid of a list of parameters; the list can be used by clients and conference interpreters for their overall and personal quality assurance.